Mesoporous silica supported bimetallic Pd/Fe for enhanced dechlorination of tetrachloroethylene. Issue 110 (23rd October 2015) - Doong, Ruey-an; Saha, Sandip; Lee, Cheng-hsien; Lin, Hong-ping
Abstract : Immobilization of Pd–Fe nanoparticles on mesoporous SiO2 microspheres increases the reactivity for tetrachloroethylene dechlorination and enhances the mobility and permeability for in situ remediation of chlorinated hydrocarbons in porous media. Abstract : In this study, mesoporous silica (SiO2 ) microspheres were hydrothermally synthesized in the presence of gelatin for the immobilization of bimetallic Pd/Fe nanoparticles (Pd–Fe/SiO2 ) to enhance the dechlorination efficiency and dechlorination rate of tetrachloroethylene (PCE) under anoxic conditions. Scanning electron microscopy images and elemental mapping showed that the distribution of nanoscale zerovalent iron (NZVI, Fe) on SiO2 was uniform and the density of Fe increased as the iron loading increased from 10 to 50 wt%. The optimized 30 wt% Fe/SiO2 particles were used to fabricate Pd–Fe/SiO2 microspheres by the electrochemical reduction of Pd ions to Pd 0 for the enhanced dechlorination of PCE under anoxic conditions. The dechlorination efficiency and rate of PCE by Fe/SiO2 was significantly enhanced in the presence of 0.5–3 wt% Pd and the pseudo-first-order rate constant ( k obs ) for PCE dechlorination by the mesoporous Pd–Fe/SiO2 microspheres increased by 2–3 orders of magnitude when compared with that of Fe/SiO2 alone. Ethane was found as the only end product with a carbon mass balance of 95–100%, showing that hydrodechlorination was the main reaction mechanism for PCE dechlorination by the Pd–Fe/SiO2 microspheres. Column experiments showed the good mobility and permeability of the mesoporous Pd–Fe/SiO2 microspheres when compared with that of pure NZVI alone. The results obtained in this study clearly show that the immobilization of bimetallic Pd–Fe nanoparticles on the mesoporous SiO2 microspheres not only increases the reactivity for the dechlorination of PCE but also enhances the mobility and permeability for in situ remediation of chlorinated hydrocarbons in porous media.